Analysis of The Utilization of Tofu Liquid Waste as a Biogas Electricity Power Plant (Case Study of BK Tofu Industry at Payakumbuh City West Sumatra) - Galuh Putra Rajabya; Novi Gusnita (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
The increase in population from year to year causes an increase in the need for food such as Tofu. This also has an impact on the number of tofu industries in Indonesia. The tofu industry is a food industry that is in great demand by the public, raw materials are easy to find, and processing is easy. Nevertheless, it arises that the environmental problems posed by the tofu industry are waste generated from the liquid tofu waste manufacturing process. When discharged into the environment, it can cause a foul odour and pollute the environment. The utilization of tofu liquid waste into electrical resources is one of the steps that can be developed in reducing pollution and increasing electrification. Being the first step, it is necessary to study the use of biomass as a source of electricity, which includes studying the potential of resources. This study aims to determine the potential value of tofu liquid waste and electrical energy for PLTBG fuel as an effort to apply clean technology. For the method in this study using anaerobic fermentation with SuperPro Designer simulation. As a result of this study, tofu liquid waste produces methane gas (CH4) of 141.97 m3 per day and total electrical energy of 129.03 kWh. It can be concluded from this study, tofu liquid waste can be used as biogas for generator set fuel with an output power of 12,000 Watts which meets industrial electricity needs for 11.73 hours.